Super enhancers define regulatory subtypes and cell identity in neuroblastoma - Gartlgruber, Moritz; Sharma, Ashwini Kumar; Quintero, Andrés; Dreidax, Daniel; Jansky, Selina; Park, Young-Gyu; Kreth, Sina; Meder, Johanna; Dončević, Daria; Saary, Paul; Toprak, Umut H.; Ishaque, Naveed; et al. (Nature cancer, 2021)
Half of the children diagnosed with neuroblastoma (NB) have high-risk disease, disproportionately contributing to overall childhood cancer-related deaths. In addition to recurrent gene mutations, there is increasing evidence supporting the role of epigenetic deregulation in disease pathogenesis. Yet, comprehensive cis-regulatory network descriptions from NB are lacking. Here, using genome-wide H3K27ac profiles across 60 NBs, covering the different clinical and molecular subtypes, we identified four major super-enhancer-driven epigenetic subtypes and their underlying master regulatory networks.